Size variations of selected coccolith species across Cretaceous Oceanic Anoxic events: paleoceanographic implications - C. Bottini; E. Erba; G. Faucher (2015)
The geological record of the Cretaceous documents profound changes in the ocean-atmosphere system, including injection of large amounts of CO2, super-greenhouse conditions, marine eutrophication, and altered oceanic chemistry and circulation. In some cases, these extreme conditions induced intervals of prolonged global anoxia, known as Oceanic Anoxic Events (OAE)s that can be seen as natural experiments useful to decipher responses to ecosystem perturbations. Previous investigation on selected species of nannofossils through the early Aptian OAE 1a provided evidence for size reduction of B. constans, Z. erectus, D. rotatorius accompanied by deformed/malformed coccoliths of W. barnesiae ascribed to injection of large amount of volcanogenic CO2 and consequent ocean acidification. Size reduction of B. constans was also documented across the late Albian OAE 1d. In this work, we intend to test whether the same species were affected by size variation and/or deformation during other Cretaceous OAEs, namely the early Albian OAE 1b and the Cenomanian/Turonian OAE 2. The comparison of the new datasets with the data available for OAE 1a and OAE 1d, show that B. constans reacted analogously with a decrease in the mean size when threshold conditions of excess CO2 were reached, and that coccolith size returned to normal at the end of the event. On the other hand, any significant change in size of W. barnesiae was detected, suggesting that this taxon was less sensitive to stressed environmental conditions. We speculate that even if different degrees and types of paleoenvironmetal perturbations were acting during the analysed OAEs, the same factor or combination of factors probably induced coccolith dwarfism (and malformation). Available data suggest that ocean chemistry related to the amount of CO2 concentrations, played a central role in altering coccolith secretion with recurrent dwarfism during OAE 1a, OAE 1b, OAE 1d and OAE 2.